A PILOT STUDY OF THE BLACK BRITISH PROFESSIONAL ACCOUNTING EXPERIENCE - Lewis, Anton M. (European Scientific Journal, ESJ, 2015)
The purpose of this paper is to draw on the findings of a small pilot study to examine aspects of the Black accounting experience in the U.K. The study deployed a qualitative approach of in-depth semi structured interviewing in order to uncover hidden aspects of the professional working environment. The data suggests that the accountancy field is characterized by subtle, but institutionalized inequalities of race, gender, and class; several respondents perceived the professional environment as openly sexist and racist. The small sample size and use of qualitative method means, of course, that it is impossible to claim generalization for its findings; nevertheless, the data together with statistical evidence suggest that the recruitment and retention policies of accountancy must change if it wishes to be a more diverse and meritocratic profession.